DEMOCRATIC WAY TOURISM MANAGEMENT IN MAE LA NA BEST PRACTICE COMMUNITY, PANG MA PHA DISTRICT, MAE HONG SON PROVINCE - ไกรวาส กิจฐเชต; สุขหอม อาภาภรณ์; สุขผล นนทวัฒน์ (Academic Journal Phranakhon Rajabhat University, 2018)
The objectives of this study were (1) To investigate Democratic Way Tourism Management in Mae La Na Best Practice Community, Pang Ma Pha District, Mae Hong Son Province and (2) To study success factors of democratic way tourism management in Mae La Na Community. The study was conducted using qualitative research methodology by focus group and in-depth interview from key informants: community leaders, senior in a community, and others that democratically played a vital role tourism management. The qualitative data analysis was done by using with typological analysis methods. From the study of democratic way tourism management, There is a way in which all members of the community are involved in determining and decision on tourism management. Contribute to the sharing of responsibilities among members of the community. Participating in sharing the benefits of tourism both individually and public Participation in monitoring and evaluation of various tourism project/activities. For the model of Mae La Na democratic way tourism management is direct democratic way tourism management and representative democratic way tourism management. The results of the study on success factors that cause democratic way tourism management in Mae La Na Community to be effective are as follows: (1) Traditions, culture, and the wisdom of the community is an essential mechanism for uniting people in the community democratic way moreover, (2) Community leaders played an important role in supporting the community’s democratic way tourism management process. (3) Encourage villagers to participate in the direction and decision making of community tourism and (4) Distribution of benefits from tourism to improve the quality of life of community members.